POTENSI PRODUKSI MINYAK IKAN DARI JEROAN IKAN PATIN (The Potential of Fish Oil Production from Catfish Viscera) - Asmayana Iwo (Universitas Hasanuddin, 2019)
Catfish cultivation in Indonesia has continued to increase rapidly since 2008. The increase in catfish production will be accompanied by an increase in the production of catfish waste. The meat yield that can be utilized in processing catfish is only 49%, the remaining 51% is waste consisting of head, skin, offal and bone Waste has the potential to be processed into products that are more economically valuable, such as fish oil. the innards contain 93.92% of fat, the innards are the richest part of the fat than the other parts of the catfish. One extraction method that is often used in fish oil is the rendering method. The rendering method consists of dry rendering and wet rendering. The dry rendering method can produce fish oil yield greater than the wet rendering method. Fish oil purification can be done by methods I and II. Based on the number of free fatty acids, peroxide numbers, and fatty acid profiles, the best quality catfish oil is purified oil using method I.